Taharah in the Qur'an: A Study of Maudhu'i Interpretation on the Foundations of Physical and Spiritual Cleanliness - Nurul Lisam; Islamiyah Islamiyah (al-Afkar, Journal For Islamic Studies, 2026)
The Qur'an is a guideline for rules that regulate everything in human life, especially a Muslim, because there is a lot of knowledge and laws in everyday life that are very important to learn, one example is taharah which is a rule in daily activities that must be carried out by a Muslim, especially in worship. This study uses a type of qualitative research, collecting data that is not in the form of numbers, where with this qualitative research the data that the author obtains from the results of analysis through the Library Research method in the form of books, journal articles, scriptures and other scientific works. In this study, the existence of taharah verses in the Koran is discussed, analysis of verses related to taharah, and interpretation of verses. The results of the study show that the types of Taharah in the Koran are classified into two. First, taharah on the physical and physical, such as taharah from uncleanness and hadas or material such as Ma'an t}ahura or holy water. Second, what is meant by pure is not pure as discussed in terms of fiqh or it can also be said to be pure from something physical or material, such as pure from hadas and impurities. However, what is meant is purity of soul and spiritual or non-material. The law of Taharah as interpreted by Ibn Kathir and Wahbah al-Zuhayli states that purification is obligatory for anyone who wants to perform prayers (who has not been purified) and it is sunnah for those who have purified themselves.